2019
DOI: 10.1001/jamainternmed.2018.6536
|View full text |Cite|
|
Sign up to set email alerts
|

National Trends and Long-term Outcomes of Liver Transplant for Alcohol-Associated Liver Disease in the United States

Abstract: IMPORTANCE Alcohol-associated liver disease (ALD) has emerged as the most common indication for liver transplant in the United States, but data on the reasons for this increase and long-term post-liver transplant outcomes among liver transplant recipients are sparse. OBJECTIVE To characterize trends and long-term outcomes of liver transplant for ALD in the United States between 2002 and 2016. DESIGN, SETTING, AND PARTICIPANTS This multicenter, prospective, national cohort study used data from the United Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 26 publications
1
174
0
1
Order By: Relevance
“…A recent review of ALD in the United States predicted that this proportion would increase in the next decade because of the increased rates of alcohol consumption and the decreased need for LT among those with hepatitis C. (29) Additionally, changing attitudes toward LT for ALD may be contributing, especially considering the positive results of early LT for acute alcoholic hepatitis without a mandated sobriety period. (12) It is estimated that approximately 13,000 patients die from alcohol-related liver disease annually in the United States (30) with increasing deaths among those under the age of 40 years; yet, only ~2000 annually undergo LT for this indication. This suggests that there is a larger pool of patients who may benefit from LT. As the duration of abstinence is deemphasized in favor of broader psychosocial profiling, the characteristics of ALD patients on the waiting list may change and, in turn, influence WL outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of ALD in the United States predicted that this proportion would increase in the next decade because of the increased rates of alcohol consumption and the decreased need for LT among those with hepatitis C. (29) Additionally, changing attitudes toward LT for ALD may be contributing, especially considering the positive results of early LT for acute alcoholic hepatitis without a mandated sobriety period. (12) It is estimated that approximately 13,000 patients die from alcohol-related liver disease annually in the United States (30) with increasing deaths among those under the age of 40 years; yet, only ~2000 annually undergo LT for this indication. This suggests that there is a larger pool of patients who may benefit from LT. As the duration of abstinence is deemphasized in favor of broader psychosocial profiling, the characteristics of ALD patients on the waiting list may change and, in turn, influence WL outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have proven to be largely unwarranted with surveys showing that public views on donation for ALD are mostly neutral . Furthermore, posttransplant survival among patients with ALD is similar to patients without ALD with 5‐year graft and patient survival of 73%‐79% and 10‐year graft survival of 58%‐63% …”
mentioning
confidence: 99%
“…Additionally, since the publication of a landmark trial that reported favorable outcomes of early liver transplant for severe alcoholic hepatitis, there has been a significant practice change. A recent multicenter study found that the proportion of liver transplant recipients being transplanted for alcoholic liver disease (ALD) increased from 24% in 2002 to 36.7% in 2016 . Pretransplant assessment of candidates with acute alcoholic hepatitis requires comprehensive assessment of substance use disorders that cannot be optimally performed without having CD services at transplant centers.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the proportion of LTs for ALD has significantly increased . Contributing to this rise may be the consideration of early LT for select candidates with <6 months of alcohol abstinence at high risk for mortality and perceived low risk for relapse . Although the 3‐year follow‐up on transplantation of 1 multicenter cohort suggests a 17% risk for return to sustained alcohol use after transplantation, long‐term data are lacking.…”
Section: Characteristics Of Scoring Systemsmentioning
confidence: 99%